2021
DOI: 10.1177/17543371211002947
|View full text |Cite
|
Sign up to set email alerts
|

Impact of third generation synthetic turf athletic field age on surface hardness and infill depth spatial variability

Abstract: The use of synthetic turf (ST) has become a popular option for many athletic fields. Little is known about how surface hardness and infill depth spatial variability changes over time on third generation (3G) ST athletic fields. A research study was conducted to investigate the impact of field age on surface hardness and infill depth spatial variability from 12 3G ST athletic fields in Tennessee and Georgia (USA) between March 5, 2014 and April 8, 2014. The 3G ST athletic fields tested varied in fiber type incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This generally agrees with the data presented by Dickson et al. (2021), who indicated that target infill depths are commonly set to about 67% of the pile height. Individual football clubs can request slight alterations in the target depth.…”
Section: Mandatory Practices Development In the Nflsupporting
confidence: 92%
See 1 more Smart Citation
“…This generally agrees with the data presented by Dickson et al. (2021), who indicated that target infill depths are commonly set to about 67% of the pile height. Individual football clubs can request slight alterations in the target depth.…”
Section: Mandatory Practices Development In the Nflsupporting
confidence: 92%
“…Athletic play and other activities on the surface can displace the infill and otherwise disrupt constituents of the surface, such that the overall hardness of the surface may change from the as‐designed specification and variability in the localized hardness over the playing surface area may increase (Dickson et al., 2021) . In practice, then, surface hardness testing should be carried out a regular basis at all locations on the surface, and maintenance practices should be used that generate consistent values across the field surface and over time.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, participants discussed the hardness of artificial turf. Artificial turf fields can increase in hardness over time without proper maintenance and lead to increased injury rates (Dickson et al 2021;Fleming et al 2020;McMurtry and Fiedler 2019). The thermal comfort of a surface is also a crucial element and was cited by participants often.…”
Section: Discussionmentioning
confidence: 99%